Strategic decision-making in TVET higher education: Applying the fuzzy delphi technique to foster inclusive digital pedagogy in Indonesia-Malaysia - Harris Pinagaran Nasution; Mohd Ridhuan Mohd Jamil; Mohd Muslim bin Md Zalli; Vivianti Novita; Suri Purnami; Nurulrabihah Mat Noh; Nadzimah binti Idris; Nursiah, Nursiah (Universitas Negeri Yogyakarta, 2025)
The rapid digitalization of education demands inclusive pedagogical strategies, especially within Technical and Vocational Education and Training (TVET), to ensure equitable learning opportunities. This study focuses on post-secondary students and aims to identify the competencies required by educators in implementing inclusive digital pedagogy. It also serves as a foundational reference for future in-depth research. The study examines the strength of consensus among expert groups from Indonesia and Malaysia regarding inclusive digital pedagogy using the Fuzzy Delphi Technique (FDT). A purposive sampling technique was employed to select 30 experts from Indonesia and Malaysia. The selection criteria included academic qualifications, professional experience in TVET and digital pedagogy, and prior involvement in educational research or policy-making, in identifying and prioritizing key components, including infrastructure and training, digital skills development, accessibility, student-centered approaches, employer engagement, and personalized learning. Data analysis utilizing triangular fuzzy numbers revealed a strong consensus, highlighting the foundational role of infrastructure and innovative pedagogical practices aligned with industry needs. The findings contribute a comprehensive framework for enhancing digital inclusivity in Southeast Asian TVET contexts and demonstrate the effectiveness of FDT in consensus-based educational research. Future research is recommended to empirically validate the proposed framework in real classroom settings and to investigate its adaptability across different cultural environments in the ASEAN region.